Visualization of Violence against Palestine in the Digital Caricature ’Nawaftoon’ - Sakinah, Amilatun; Kasmana, Kankan; Isfiaty, Tiara (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
The humanitarian tragedy in Palestine perpetrated by Israel still continues. The cruelty of this occupation is being covered up by killing journalists and censoring social media. This will result in a reduction in the amount of information available about Israel’s occupation of Palestine. If this is allowed to continue, the world’s attention to Palestine could disappear. Therefore, research on Nawaftoon’s caricatures is important because they focus on exposing Israel’s brutality towards Palestine. This study aims to analyze how violence is visualized in a Palestine-themed poster. This research uses Gunther Kress and Theo van Leeuwen’s social semiotics approach through representational, interactive, and compositional meaning analysis. The results of the analysis show that Nawaftoon’s caricature depicts Israel’s violence, and simplifies the complexity of Israel’s occupation of Palestine so that it reinforces the narrative of cruelty and the brutality of Israel’s colonization towards Palestine, and also reinforces the narrative of Palestinian resistance. The caricatures clearly identify the perpetrators and frame the actual events in a direct way through specific color, symbolism, and character representation. These findings reveal that such visual elements function not only as illustrations but also as a form of accessible documentation that simplifies complicated events and makes them more comprehensible to the public. Thus, these images play a crucial role in countering media censorship and redirecting public attention toward the humanitarian crisis in Gaza, particularly amid the turmoil of ongoing political events.